High Power Microwave Breakdown Study - Holmquist, David (My University, 2011)
In this research a rapidly forming (<50 ns) self-initiating distributed plasma discharge was observed using an X-band (WR-90) microwaves. We also observed slower forming (300-400 nS) plasma breakdown with 1 kHz repeated 800 nS microsecond pulses. Visual plasma formation was observed with a variety of high power reputation rates. The microwave discharge test chamber is an L-band (WR-650) rectangular waveguide with polycarbonate windows. The chamber is illuminated by the output of a 25 kW, 9.382 GHz magnetron with an X-band waveguide pressed against the chamber window. I filled the chamber with Ne, Ar, and mixtures of Ne and Ar. Singles pulse of 0.8 us along with 1 kHz repeated microsecond pulses were investigated. The objective of the experiment was to study conditions and configurations enabling rapid discharge formation with gas configuration, pressure, and pulse variety as different input parameters. The goal was to significantly attenuate the transmission signal on less than 100 nS time scales and visually observe the breakdown process with an ultra high speed ICCD camera.